A cluster-randomized, controlled trial of nutritional supplementation and promotion of responsive parenting in Madagascar: the MAHAY study design and rationale - Lia C. H. Fernald; Emanuela Galasso; Jumana Qamruddin; Christian Ranaivoson; Lisy Ratsifandrihamanana; Christine P. Stewart; Ann M. Weber (BMC, 2016)
Abstract Background Over half of the world's children suffer from poor nutrition, and as a consequence they experience delays in physical and mental health, and cognitive development. There is little data evaluating the effects of delivery of lipid-based, nutrition supplementation on growth and development during pregnancy and early childhood within the context of a scaled-up program. Furthermore, there is limited evidence on effects of scaled-up, home-visiting programs that focus on the promotion of child development within the context of an existing, national nutrition program. Methods/Design The MAHAY ("smart" in Malagasy) study uses a multi-arm randomized-controlled trial (RCT) to test the effects and cost-effectiveness of combined interventions to address chronic malnutrition and poor child development. The arms of the trial are: (T0) existing program with monthly growth monitoring and nutritional/hygiene education; (T1) is T0 + home visits for intensive nutrition counseling within a behavior change framework; (T2) is T1 + lipid-based supplementation (LNS) for children 6-18 months old; (T3) is T2 + LNS supplementation of pregnant/lactating women; and (T4) is T1 + intensive home visiting program to support child development. There are anticipated to be n = 25 communities in each arm (n = 1250 pregnant women, n = 1250 children 0-6 months old, and n = 1250 children 6-18 months old). Primary outcomes include growth (length/height-for-age z-scores) and child development (mental, motor and social development). Secondary outcomes include care-giver reported child morbidity, household food security and diet diversity, micro-nutrient status, maternal knowledge of child care and feeding practices, and home stimulation practices. We will estimate unadjusted and adjusted intention-to-treat effects. Study protocols have been reviewed and approved by the Malagasy Ethics Committee at the Ministry of Health in Madagascar and by the institutional review board at the University of California, Davis. This study is funded by the Strategic Impact Evaluation Fund (SIEF), the World Bank Innovation Grant, the Early Learning Partnership Grant, the Japan Scaling-up for Nutrition Trustfund, and Grand Challenges Canada. The implementation of the study is financed by Madagascar's National Nutrition Office. Trial registration Current Controlled Trials ISRCTN14393738 . Registered June 23, 2015.